2006
DOI: 10.1088/0967-3334/27/7/003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance spectroscopy and the diagnosis of bladder pathology

Abstract: Bladder pathology is usually investigated visually by cystoscopy. At present, definitive diagnosis of the bladder can be made by biopsy only, usually under general anaesthesia. This is a relatively high-cost procedure in terms of both time and money and is associated with discomfort for the patient and morbidity. Thus, we used an electrical impedance spectroscopy technique for differentiating pathological changes in the urothelium and improving cystoscopic detection. For ex vivo study, a whole or part of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…Jossinet compared the complex impedance loci of normal and carcinoma in a frequency range of 488 Hz to 1 MHz and an obvious difference was observed in the shape and location of the loci at frequencies above 125 kHz for normal, benign and carcinoma tissue. Keshtkar et al performed electrical impedance measurements on 38 invivo benign and malignant subjects at a frequency range of 2-348 kHz [20]. The results revealed that the impeditivity of malignant subjects were significantly higher than the impeditivity of benign subjects which was in contrast to the results presented by Brown et al [21] and Gonzales-Correa [22].…”
Section: Introductionmentioning
confidence: 92%
“…Jossinet compared the complex impedance loci of normal and carcinoma in a frequency range of 488 Hz to 1 MHz and an obvious difference was observed in the shape and location of the loci at frequencies above 125 kHz for normal, benign and carcinoma tissue. Keshtkar et al performed electrical impedance measurements on 38 invivo benign and malignant subjects at a frequency range of 2-348 kHz [20]. The results revealed that the impeditivity of malignant subjects were significantly higher than the impeditivity of benign subjects which was in contrast to the results presented by Brown et al [21] and Gonzales-Correa [22].…”
Section: Introductionmentioning
confidence: 92%
“…the impedance spectra) obtained from the model with those obtained experimentally for both normal and malignant cases. There is a study by authors that explains how we can measure the electrical impedance data of the human bladder tissue [7]. However, the current flowing through every node located on the boundary midway between the two drive electrodes can also be calculated and then integrated to give the total current flowing through each layer.…”
Section: Methodsmentioning
confidence: 99%
“…However, authors carried out a study about the bio impedance measurement of the bladder tissue [7] and introduced the electrical impedance spectroscopy as a new technique to detect of bladder pathology. Then, they modelled the current distribution inside the normal and malignant human urothelium and discussed about this modelled results according to the current distribution in different layers of the urothelium [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported significant differences in electrical impedance, using the EIS devices, between dissimilar cells or tissues from various organs. [12][13][14][15][16][17] Despite the availability of EIS probes in tumor detection, it is inappropriate for detecting completely buried endophytic tumors and estimating tumor depth from the surface of the organ. On the other hand, the lEoN is a needle with EIS incorporated on its tip, which enables the device to penetrate through the tissues and reach the tumor, as well as the deepest margin between the tumor and normal tissues.…”
Section: Introductionmentioning
confidence: 99%